2008
DOI: 10.1002/elps.200800128
|View full text |Cite
|
Sign up to set email alerts
|

Non‐uniform surface charge distributions in CE: Theoretical and experimental approach based on Taylor dispersion

Abstract: The control of the EOF direction and magnitude remains one of the more challenging issues for the optimization of separations in CE. In this work, we investigated the possibility to use non-uniform surface charge distribution for the modulation of the EOF in CE. Non-uniform zeta potentials were obtained by modifying a section of the capillary surface using adsorption of polyelectrolytes. Three different methods were studied: (i) partial polycation coating on a fused silica capillary, (ii) partial polycation (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…It is also important to notice that, in these experimental conditions, the maximal oligonucleotide injection volume cannot exceed 50% of the total volume of the capillary otherwise the oligonucleotide plug moves toward the outlet side of the capillary (toward the detector) even though the conductivity is the same in both compartments (BGE1 compartment and ON compartment). It is well known that in the presence of two different zones, in a bare‐fused silica capillary, the average solvent flow is equal to the average of the electroosmotic mobilities of each zone, weighted by the relative lengths of the zones . Then, we can assume that the electroosmotic mobility in ON compartment is higher than the electroosmotic mobility in the BGE1 compartment.…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to notice that, in these experimental conditions, the maximal oligonucleotide injection volume cannot exceed 50% of the total volume of the capillary otherwise the oligonucleotide plug moves toward the outlet side of the capillary (toward the detector) even though the conductivity is the same in both compartments (BGE1 compartment and ON compartment). It is well known that in the presence of two different zones, in a bare‐fused silica capillary, the average solvent flow is equal to the average of the electroosmotic mobilities of each zone, weighted by the relative lengths of the zones . Then, we can assume that the electroosmotic mobility in ON compartment is higher than the electroosmotic mobility in the BGE1 compartment.…”
Section: Resultsmentioning
confidence: 99%
“…The use of charged polyelectrolytes for capillary coating has become popular in CE, especially for peptides and proteins analysis to prevent analyte adsorption [43][44][45][46][47][48][49][50] and to control the EOF [51][52][53][54]. The polyelectrolytes are generally highly adsorbed to the capillary via electrostatic, hydrogen and even hydrophobic interactions [10,17,18,22,23,[55][56][57].…”
Section: Pdadmac-coated Capillarymentioning
confidence: 99%
“…The authors 43 investigated the possibility to use nonuniform surface charge distribution for the modulation of the EOF in CE. They found that the combination of a partially coated capillary with a LVSS preconcentration step can be used for injecting up to 95% of the capillary volume.…”
Section: Kohlrausch Adjustment Of Concentrationmentioning
confidence: 99%